Empirical research on the impact of green credit development on the profitability of commercial banks - Wu, Renhong; Fang, Yuantao; Hossain, Md Alamgir; Wu, Aocheng (Asian Development Policy Review, 2024)
This paper examines empirical research on the impact of green credit development on commercial banks’ probability. To promote the green transformation of the economy, the efficient use of resources, and the effective improvement of the ecological environment, it is necessary to vigorously promote the comprehensive development of green finance and the continuous improvement of the green financial system. In terms of improving the green financial system, efforts can start with green credit. This paper uses related data from 10 Chinese listed commercial banks from 2012 to 2020 as panel data, and employs Stata software for empirical research and analysis. The final empirical results show that launching a green credit business may, in the short term, lead to a decrease in the bank's profitability. The reason for this result may be that China has started developing green finance relatively late and for a shorter duration, so the time and number of entities selected for data are very limited. Moreover, the expansion of the green credit business means that while suppressing "two highs and one surplus" enterprises, it also leads to a significant reduction in their loans, thus affecting the profitability of commercial banks. Ultimately, we propose targeted suggestions that align with China’s national conditions and enhance the green credit system.